2015
DOI: 10.1002/ejlt.201400535
|View full text |Cite
|
Sign up to set email alerts
|

Analytical approaches for measuring pesticides, mycotoxins and heavy metals in vegetable oils: A review

Abstract: Nowadays, consumers are concerned about the toxicological implications and in a great demand for more information about the presence of organic residues and contaminants in vegetable oils. Pesticide residues, mycotoxins, and heavy metals can be readily accumulated in vegetable oil during the cultivation, processing and storage. Those chemical contaminants or its metabolites are carcinogenic, teratogenic, and immunotoxic, which result in serious damages to human health. With public health and economic losses co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 66 publications
(65 reference statements)
0
10
0
Order By: Relevance
“…They are characterized by a different source of origin, chemical structures, formulation, toxicity, mode of entry and action. [10,11]. Furthermore, they can contaminate the surrounding environment or even bioaccumulate.…”
Section: Introductionmentioning
confidence: 99%
“…They are characterized by a different source of origin, chemical structures, formulation, toxicity, mode of entry and action. [10,11]. Furthermore, they can contaminate the surrounding environment or even bioaccumulate.…”
Section: Introductionmentioning
confidence: 99%
“…Both gas chromatography (GC) (Guardia-Rubio et al 2006, López-Feria et al 2009, Deme et al 2014, He et al 2017, Parrilla Vázquez et al 2016) and liquid chromatography (LC) (Gilbert-López et al 2010, Sobhanzadeh et al 2011, Polgár et al 2012, Moreno-González et al 2014) coupled with mass spectrometry (MS), or tandem mass spectrometry (MS/ MS) detection, are widely used for the determination of pesticides in vegetable oils. Nevertheless, less selective highperformance liquid chromatography with diode array detector (HPLC-DAD) was also successfully applied to the analysis of pesticide residues in edible oils (Jaabiri et al 2013, Ma et al 2016). Stoev and Stoyanov (2007) concluded that the reliability of identification of an analyte by DAD is comparable to the reliability of identification by low resolution MS-MS.…”
Section: Introductionmentioning
confidence: 99%
“…However, they are expensive and need a larger amount of time for sample preparation before analysis, which has inhibited extending the scope of monitoring, particularly in field-screening scenarios [ 9 ]. As an alternative, broad-specificity immunoassays are extraordinarily effective for monitoring and detecting samples of multi-analyte residues in food and environmental samples [ 10 , 11 ], and the development of broad-specificity immunoassays demands the preparation of a broad spectrum of antibody specificity to all target analytes. For example, several attempts have been made to develop broad-specificity immunoassays for OP pesticide residues by the production of a broad-spectrum-specific antibody against OP pesticide [ 12 ].…”
Section: Introductionmentioning
confidence: 99%